Regional prevalence of different types of sinusitis at a tertiary care centre in Northern India - Khan, Abdul Rehman; Siddiqui, Farzana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The aim of the study was to determine the incidence of different types of rhinosinusitis in patients attending ENT Department OPD at a tertiary care centre in Ruhelkhand area of Northern India. Methods: This study was done at department of Otorhinolaryngology, RMRI, Bareilly, India, a tertiary-care Teaching hospital. A total number of 39823 patients (22379 females, 17444 males) were included in this study from December 2017 till February 2020. Age range of selected patients was 3 months to 76 years, 3883 patients were having Rhinosinusitis and remaining having other ENT diseases. Results: During 27 months period from December 2017 to February 2020, 39823 patients were seen in the OPD and patients were categorized in different disease groups, like chronic suppurative otitis media and acute suppurative otitis media, upper respiratory tract infections, acute and chronic tonsillitis and pharyngitis. Fourth most common disease group was different types of rhinosinusitis. Conclusions: In this study assessment was done of different ENT patients attending OPD. Chronic rhinosinusitis (46.1%) was the most common type of rhinosinusitis, followed by Acute type (29.7%).